K-Shell Double Photoionization Cross Section of (Be, Mg and Ca) Atoms - A. Khalf , Ala'a (University of Thi-Qar Journal of Science, 2012)
Double photoionization cross sections has been calculated using Hartree-Dirac-Slater method for Be, Ca and Mg atoms, the result were compared with Colgan et.al and Kheifets et.al theoretical data. Experimental measurements of photoioniztion cross sections was not available in order to make a comparison with our calculations. In general our results of the photoionization cross sections gave a good match with the theoretical data that compared with for Be and Ca atoms specially at high energies, and the same behavior for Mg atom but with no matching